Regional Investment Pioneers in South Asia : The Payoff of Knowing Your Neighbors - Kathuria, Sanjay; Yatawara, Ravindra A.; Zhu, Xiao’ou (Washington, DC: World Bank, 2021)
Regional economic engagement within South Asia may gain increasing importance owing to several factors that are currently in play, including strategies to diversify global value chains and locate such value chains nearer home. These developments offer South Asia a chance to enhance its low levels of regional economic engagement and capitalize on significant unrealized development opportunities. This report shows that examining intraregional investment and knowledge connectivity enhances our understanding of the low levels of intraregional trade and limited regional value chains in South Asia. Creating a new and unique data set for South Asian investment, it provides a detailed and nuanced understanding of the drivers of outward investment, both regional and global, for South Asian firms. “Regional Investment Pioneers in South Asia” provides key considerations for policy makers in South Asia, which remain particularly relevant in the aftermath of the pandemic. First, it makes a case for regulatory relaxation of outward FDI regimes, based on new micro foundations, grounded in value chains. Second, it spells out details of smart inward FDI promotion techniques and investment facilitation. Third, it identifies distinct cross-border information-enhancing and network development activities. Fourth, it suggests that digital connectivity and continued interventions in reducing trade costs are warranted to increase investment as well as trade flows. There is particular scope to build on the digitalization initiatives in trade and investment facilitation taken during the pandemic. “Regional Investment Pioneers in South Asia” follows on, and is complementary to, the earlier World Bank report, “A Glass Half Full: the Promise of Regional Trade in South Asia.”